Mobile game for active learning - Tan, Xian Jun (2016)
Games as educational tools are slowly gaining popularity in society. Gamification of human behavior is a growing field that deserves more exploration. The objective of the project is to create a social learning experience for students in the form of a game, as well as an assessment platform for the educator. The educator should be able to gauge his students’ understanding and learning speed via the project, and the students should be motivated to learn due to the game. The game was created using the Unity platform using C# as the programming language, and the data for the educator was stored on an online database. The game was designed with both the educator and the students in mind, taking in account their preferences and their motivations. The result of the project is a robust mobile application capable of handling the number of students required. The project was designed to engage the students’ attention and its functionality and gameplay serve this purpose. The project was an educational experience and the concept of a game that combines teaching, learning and playing is an area that deserves more attention. A niche exists for an all-purpose quizzing platform for educators and I believe it is an area with great potential.